2014
DOI: 10.1007/s00464-014-3766-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between intraoperative cholangiography and choledochoscopy for ductal clearance in laparoscopic CBD exploration: a prospective randomized study

Abstract: The present study showed that intraoperative choledochoscopy is better than IOC for determining ductal clearance after transcholedochal LCBDE and is less cumbersome and less time-consuming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 50 publications
1
20
0
1
Order By: Relevance
“…In a study comparing this technique with IOC, significant differences were found only in the operating time; however, a 3 % false-positive rate was obtained for the IOC group, who required a choledochoscopy. The authors concluded that choledochoscopy was better than IOC for confirming CBD clearance [28]. This instrument was not available in our hospital during the study period, but our group has extensive experience in interpreting IOCs, and we detected no false-positive cases among our patients.…”
Section: %)mentioning
confidence: 69%
“…In a study comparing this technique with IOC, significant differences were found only in the operating time; however, a 3 % false-positive rate was obtained for the IOC group, who required a choledochoscopy. The authors concluded that choledochoscopy was better than IOC for confirming CBD clearance [28]. This instrument was not available in our hospital during the study period, but our group has extensive experience in interpreting IOCs, and we detected no false-positive cases among our patients.…”
Section: %)mentioning
confidence: 69%
“…Information from imaging studies contributes to decision-making regarding the method of stone removal. The choledochoscopic technique provides direct visualization during the process of stone removal, which is beneficial for judging the status of the stones and increasing the success rate of stone clearance [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…With the development of technology, LCBDE, as an extension of LC, since it was first reported in the 1990s, has been proven to be safe, effective, and minimally invasive, and it does not cause damage to the sphincter of Oddi [1,2,17,19]. Aawsaj et al [8] reported that laparoscopy combined with choledochoscopy is an effective, feasible, and safe technique for the treatment of concomitant gallbladder stones and CBD stones and is associated with fewer complications.…”
Section: Discussionmentioning
confidence: 99%